Detasseling on maize grain yield - Rosa, Antonio Paulo Moro da; Mundstock, Cláudio Mario (Pesquisa Agropecuaria Brasileira, 2014)
Detasseling effects on a maize hybrid (Zea mays L.) in a field experiment established at Guaíba, Rio Grande do Sul, Brazil were studied. Tassel removal was performed at fifteen, nine and four days before anthesis and during anthesis. Detasseling always outyielded the checkplot (6.220 kg/ha). The highest yield (7.590 kg/ha) was obtained with the treatment applied nine days before anthesis, decreasing with the previous and later dates. Yield increase was mainly due to a higher number of grains produced per ear and also to a small increase in ear number.